Prospective study on technique of graft fishing with anterior tucking in type 1 tympanoplasty and its hearing outcome - Patni, Digant; Mishra, Ankit; Patel, Dinesh; Munjal, Vishal R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media (COM) is a common health problem in developing world and has a major impact on patient in the form of hearing loss. Temporalis fascia is commonest graft material used for tympanoplasty as it is readily available through same post aural incision. The study was conducted with an aim to find out the effectiveness of fishing technique and anterior tucking in terms of graft stability, graft uptake, hearing improvement and complications. Methods: The present study is prospective study conducted on patients with complains of otorrhea and hearing loss, of age between 15 to 60 years, during the period January 2017 to June 2018. Patients with inactive mucosal COM and pure conductive hearing loss who underwent type-I tympanoplasty were included. Patients with cholesteatoma, ossicular pathology, trauma, mixed or sensorineural hearing loss, were excluded. Paired ‘t’ test was applied to compare preoperative and postoperative mean air-bone gap. Results: In our study total 123 patients were analysed for the follow-up period of 6 months and it was observed that graft was well accepted in 93.5% patients while in 4.8% patients residual anterior perforation was found and in 1.7% patients the graft was completely rejected, showing an overall success rate at the end of 6 months follow-up to be 93.5%. There was a statistically significant improvement in hearing gain at the end of 6 months follow-up (p<0.05). Conclusions: Tympanoplasty with temporalis fascia graft using fishing and anterior tucking technique gave good dimensional stability to graft, preventing lateralization / medialization of graft. The superiorly based circumferential flap allowed for 360 degree placement of graft and anterior tucking, with overall high success rate and lower rate of complications and graft rejection.